Manufacturing Characteristics of Probiotic Esherichia Coli Strain M-17 After Immobilization in Gel Carriers and Storage at Various Low Temperatures - Petrov, Ilya; Vysekantsev , Igor; Cherkashina, Yana; Peretyatko, Olena; Yagniuk, Yuliia (Problems of Cryobiology and Cryomedicine, 2021)
Probl Cryobiol Cryomed 2021; 31(3): 273–276